2016
DOI: 10.1111/acem.12908
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Dedicated, Non–Physician‐led Mental Health Team to Reduce Pediatric Emergency Department Lengths of Stay

Abstract: Objectives: Utilization of emergency departments (EDs) for pediatric mental health (MH) complaints is increasing. These patients require more resources and have higher admission rates than those with nonpsychiatric complaints.Methods: A multistage, multidisciplinary process to reduce length of stay (LOS) and improve the quality of care for patients with psychiatric complaints was performed at a tertiary care children's hospital's ED using Lean methodology. This process resulted in the implementation of a dedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(99 citation statements)
references
References 22 publications
1
90
0
8
Order By: Relevance
“…Of the 16 studies, 11 studies were conducted in particular health care units (Arad et al, 2007;Dellenmark-Blom & Wigert 2014;Ekim & Ocakci 2016;Gallotto et al, 2019;Góes & Cabral 2017;Lerret et al, 2017;Meerlo-Habing et al, 2009;Pfeil et al, 2007;Schuh et al, 2016;Wells et al, 2017;Smith et al, 2018), 4 in acute medical setups Holland et al, 2014Holland et al, , 2015Weiss et al, 2017), and one in an Emergency Department (Uspal et al, 2016). Of the 16 studies, five studies included nurses' involvement in the post-discharge period Lerret et al 2017;Meerlo-Habing et al, 2009;Pfeil et al, 2007;Wells et al, 2017), eight studies included about nurses' involvement before the hospital discharge (Arad et al, 2007;Gallotto et al, 2019;Góes & Cabral 2017;Holland et al, 2014Holland et al, , 2015Schuh et al, 2016;Weiss et al, 2017;Smith et al, 2018), and 2 studies described both pre-discharge and post-discharge involvement of the nurse (Dellenmark-Blom & Wigert 2014;Ekim & Ocakci 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 16 studies, 11 studies were conducted in particular health care units (Arad et al, 2007;Dellenmark-Blom & Wigert 2014;Ekim & Ocakci 2016;Gallotto et al, 2019;Góes & Cabral 2017;Lerret et al, 2017;Meerlo-Habing et al, 2009;Pfeil et al, 2007;Schuh et al, 2016;Wells et al, 2017;Smith et al, 2018), 4 in acute medical setups Holland et al, 2014Holland et al, , 2015Weiss et al, 2017), and one in an Emergency Department (Uspal et al, 2016). Of the 16 studies, five studies included nurses' involvement in the post-discharge period Lerret et al 2017;Meerlo-Habing et al, 2009;Pfeil et al, 2007;Wells et al, 2017), eight studies included about nurses' involvement before the hospital discharge (Arad et al, 2007;Gallotto et al, 2019;Góes & Cabral 2017;Holland et al, 2014Holland et al, , 2015Schuh et al, 2016;Weiss et al, 2017;Smith et al, 2018), and 2 studies described both pre-discharge and post-discharge involvement of the nurse (Dellenmark-Blom & Wigert 2014;Ekim & Ocakci 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Efficient collaboration with health providers inside the hospital will allow more opportunities for nurses to involve in the patient discharge planning, which increases patient and family satisfaction Góes & Cabral 2017;Holland et al, 2015;Uspal et al, 2016;Smith et al, 2018). This collaborative work will work towards speeding up the recovery of the child (Wells et al, 2017).…”
Section: In-hospital Medical Teammentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies used the Lean Thinking, Multidisciplinary, and Statistics approach. Uspal et al [ 65 ] found a significant reduction in the mean length of hospital stay of pediatric patients with psychiatric complaints and the best perception of Emergency Department care staff. Finally, Ref.…”
Section: Research Problems Approaches and Applied Toolsmentioning
confidence: 99%
“…Patients discharge has also been improved by as much as 40% [ 62 ]. Remote scheduling avoids aggravating oncology patients’ clinical condition creating reductions in displacement and waiting time [ 65 , 66 ]. Implementing a new layout is another benefit that positively impacts the organization’s activities and patient flow [ 16 ].…”
Section: Benefits Of Lean Application In Emergency Departmentsmentioning
confidence: 99%